The complete chloroplast genome of Fagus crenata (subgenus Fagus ) and comparison with F. engleriana (subgenus Engleriana ) - Worth, James R. P.; Liu, Luxian; Wei, Fu-Jin; Tomaru, Nobuhiro (PeerJ (San Francisco, CA), 2019)
This study reports the whole chloroplast genome of Fagus crenata (subgenus Fagus ), a foundation tree species of Japanese temperate forests. The genome has a total of 158,227 bp containing 111 genes, including 76 protein-coding genes, 31 tRNA genes and 4 ribosomal RNA genes. Comparison with the only other published Fagus chloroplast genome, F. engeleriana (subgenus Engleriana ) shows that the genomes are relatively conserved with no inversions or rearrangements observed while the proportion of nucleotide sites differing between the two species was equal to 0.0018. The six most variable regions were, in increasing order of variability, psb K- psb I, trn G- psb fM, rpl 32, trn V, ndh I- ndh and ndhD - psa C. These highly variable chloroplast regions in addition to 160 chloroplast microsatellites identified (of which 46 were variable between the two species) will provide useful genetic resources for studies of the inter- and intra-specific genetic structure and diversity of this important northern hemisphere tree genus.